REGIOSELECTIVE SYNTHESIS AND ANTIMICROBIAL ACTIVITY OF O-ALKYLATED PHYSCION'S DERIVATIVES - MANOJLOVIC,N (Sociedad Chilena de Química, 2007)
Regioselectivity in the reaction of microwave promoted O-alkylation of physcion in the presence of montmorillonite clay K-10 was discussed. The mechanism of formation of corresponding anions of physcion was investigated using semiempirical molecular-orbital methods. The results of antibacterial and antifungal activity of the obtained derivatives showed that the introduction of different substituents (OCF£3, OCH2C(CH3)=CH2, OCH2CH2CH3 and OCH2C6H5), at the C-1 and C-8 atoms led to a remarkable change in their antimicrobial activity